'We're In This Together:' neoliberalism and the disruption of the coach/athlete hierarchy in CrossFit. Issue 1 (2nd January 2016) - Heywood, Leslie
Abstract: CrossFit is a growing model of fitness that defines itself in opposition to conventional fitness practices. "Specializing in not specializing", CrossFit aims to provide a General Physical Preparedness programme sustainable and scalable across an athlete's life course. "Fitness" is achievable through "constantly varied high intensity functional movements performed across broad time and modal domains". A differential modality of time is operational in CrossFit, which includes the "clock time" of earlier eras but is largely characterised by the "network time" that makes CrossFit omnipresent. Characterised by the neoliberal rhetoric of self-improvement and individual responsibility, CrossFit takes these ideas one step further by extending its practice and philosophy to every aspect of an athlete's life, including their network of personal relationships. CrossFit's lack of specialisation and articulation within network time function to shift the role of the coach from central authority to one who performs affective, emotional labour and forms of a "relationship" that involves supporting each individual athlete in the achievement of their own goals inside and outside "the box".